2021
DOI: 10.1021/acs.jafc.1c04022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of Novel Antifungal Leads: 3,5-Dichlorobenzyl Ester Derivatives

Abstract: Succinate dehydrogenase (SDH) is one of the most important molecular targets for the development of new fungicides. Carboxamide fungicides are a class of SDH inhibitors widely used to inhibit highly destructive plant pathogens. Although cases of resistance have been found in fungal pathogens due to the unrestricted use in recent years, there is still demand for new compounds with improved fungicidal activity. Therefore, a series of ester compounds were designed to investigate potential novel antifungal molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The mycelial growth rates method ( Du et al, 2021 ; Wang S. et al, 2021 ) was selected to evaluate the antifungal activities of the compounds 5a–5r against six phytopathogenic fungi, including cucumber Botrytis cinerea , tobacco Botrytis cinerea , blueberry Botrytis cinerea , Phytophthora infestans , strawberry Botrytis cinerea , and Pyricularia oryzae Cav. The tested compounds were dissolved in 0.5 ml dimethyl formamide (DMF) and then added 9.5 ml sterile water to prepare the test liquids.…”
Section: Methodsmentioning
confidence: 99%
“…The mycelial growth rates method ( Du et al, 2021 ; Wang S. et al, 2021 ) was selected to evaluate the antifungal activities of the compounds 5a–5r against six phytopathogenic fungi, including cucumber Botrytis cinerea , tobacco Botrytis cinerea , blueberry Botrytis cinerea , Phytophthora infestans , strawberry Botrytis cinerea , and Pyricularia oryzae Cav. The tested compounds were dissolved in 0.5 ml dimethyl formamide (DMF) and then added 9.5 ml sterile water to prepare the test liquids.…”
Section: Methodsmentioning
confidence: 99%
“…Further study revealed that compound 84 had weaker binding to the target compared to boscalid, which was consistent with findings of inhibitory activity of SDH, even though it had similar effects to boscalid. 120 This work indicated that this kind of ester compound might be novel lead compound of SDHIs and replacing amides with esters could be a successful strategy in research and development of novel SDHIs fungicides.…”
Section: Journal Ofmentioning
confidence: 99%
“…The antifungal activities against Botryosphaeria dothidea (B. dothidea), Phompsis sp., Botrytis cinereal (B. cinerea), Colletotrichum gloeosporioides (C. gloeosporioides), Pyricutaria oryzae (P. oryzae), and Sclerotinia sclerotiorum (S. sclerotiorum) of compounds 5a-5w at 50 μg/ml were determined by the typical mycelium growth rate method (Du et al, 2021;Wang W. et al, 2021), and tebuconazole was used as a positive control.…”
Section: In Vitro Antifungal Activity Testmentioning
confidence: 99%